Trends and correlates of the time spent playing videogames in Italian children and adolescents - Simone Amendola (Mediterranean Journal of Clinical Psychology, 2021)
Background: The use of electronic devices and screen-time behaviours among young people have increased in the last two decades. However, empirical evidence on trends in time spent playing videogames among Italian youths is lacking. The present study examined trends and correlates of the time spent by children and adolescents playing videogames in Italy between 2006 and 2014.